PENDAMPINGAN PUBLIKASI MASYARAKAT ILMIAH SEBAGAI SOLUSI PRAKTIS MELALUI WEBINAR: KUPAS TUNTAS RAHASIA LOLOS JUPELAKNAS - Ira Wulan Sari; Fanny Fanny Adibah (As-Sidanah, 2022)
Writing scientific articles is one of the things that are mandatory for the scientific community according to its objectives. This community service activity is in the form of a secret peeling webinar activity that passes the National Education Training Center which aims to provide additional education related to professional and academic competencies for the scientific community and become a practical solution for publication for the scientific community. The scientific community in question is people who are in academia, such as teachers (teachers and lecturers), researchers, and students. This activity was attended by 52 participants from various professions and regions. In seeing the success of the objectives of this activity through data collection and analysis techniques in the form of video recording documentation of activities, observations and questionnaire responses of participants were carried out in a qualitative descriptive manner. In the implementation of this webinar activity, it was quite successful in becoming a practical solution for publications for the scientific community, by showing the number of webinar participants attending more than 70% of the total number of registrants, there was a match between the planning and implementation stages, as well as the results of the participant's response questionnaire with average results. more than 80% responded positively. As an alternative solution based on the results of the discussion and Q&A from the webinar activity, these are (a) mentally prepare; (b) pay attention to the ethics of writing and publication; (c) the strategy for selecting journals and their publications by taking into account the selection of journals following the scope of the titles of the articles that have been made, and using a template according to the provisions of the journal we have chosen; (d) strategies in writing good and correct scientific articles.